Overexpression of Na+/Ca2+ exchanger 1 display enhanced relaxation in the gastric fundus - Yasuyuki Fujimoto; Satomi Hayashi; Yasu-Taka Azuma; Kazunori Mukai; Kazuhiro Nishiyama; Satomi Kita; Ai Morioka; Hidemitsu Nakajima; Takahiro Iwamoto; Tadayoshi Takeuchi (Elsevier, 2016)
In gastric smooth muscles, the released Ca2+ activates the contractile proteins and Ca2+ taken up from the cytosol cause relaxation. The Na+/Ca2+ exchanger (NCX) is an antiporter membrane protein that controls Ca2+ influx and efflux across the membrane. However, the possible relation of NCX in gastric fundus motility is largely unknown. Here, we investigated electric field stimulation (EFS)-induced relaxations in the circular muscles of the gastric fundus in smooth muscle-specific NCX1 transgenic mice (Tg). EFS caused a bi-phasic response, transient and sustained relaxation. The sustained relaxation prolonged for an extended period after the end of the stimulus. EFS-induced transient relaxation and sustained relaxation were greater in Tg than in wild-type mice (WT). Disruption of nitric oxide component by N-nitro-l-arginine, EFS-induced transient and sustained relaxations caused still marked in Tg compared to WT. Inhibition of PACAP by antagonist, EFS-induced sustained relaxation in Tg was not seen, similar to WT. Nevertheless, transient relaxation remained more pronounced in Tg than in WT. Next, we examined responses to NO and PACAP in smooth muscles. The magnitudes of NOR-1, which generates NO, and PACAP-induced relaxations were greater in Tg than in WT. In this study, we demonstrate that NCX1 regulates gastric fundus motility.